The Existence of “PTUN” as Judicial Power Institution in Indonesia (A Comparative Study of Institutional Format) - Shafira Arizka Maulidyna (Arena Hukum, 2025)
As Strong’s study, the sharp difference between the common law and the civil law is the existence of an administrative judiciary (“Peradilan Tata Usaha Negara” / PTUN). Indonesia has a special affinity for the habits of civil law countries, but the implementation of PTUN actually tends to adopt the common law state. The legal issues in this study are : 1) what is the institutional comparation between the PTUN and other countries; and 2) what is the position of the PTUN as the implementer of judicial power in carrying out the function of resolving administrative disputes in Indonesia. Different with previous research, this study focuses on the institutional aspect to see the extent legal traditions influence the format and pattern of the PTUN in Indonesia. This normative research uses a conceptual approach, statute approach and comparative studies. As a contribution to overseas readers, this research compares the PTUN in Indonesia with administrative court in France, Netherlands, Germany, Thailand, United States. The format of the administrative court institution is not only associated with the characteristic factors of the legal system, but also by looking at the historical factors. The main feature of the administrative court is the existence of a jurisdictional distinction compare to the ordinary courts. Since the format is not well known in Indonesia, so there are many weaknesses in practice, especially related to executory functions. Reconstruction is needed to increase the effectiveness of PTUN through expanding competence to increase the authority of PTUN.